Lucas Cranach the Elder : art and devotion of the German Reformation - Noble, Bonnie (University Press of America, 2009)
Lucas Cranach the Elder (1472-1553) is the most influential painter of the German Reformation. In collaboration with Martin Luther (1483-1546), Cranach produced innovative paintings which made the complex ideas of Lutheran Christianity understandable toa wide range of viewers and inspired later generations of artists. Despite Cranach's crucial role as an interpreter of Lutheran ideas, his Reformation paintings remain unfamiliar to many American scholars. Lucas Cranach the Elder: Art and Devotion of the German Reformation presents Cranach's Reformation painting to a broader audience and explain.